2010
DOI: 10.1001/archinternmed.2010.73
|View full text |Cite|
|
Sign up to set email alerts
|

Proton Pump Inhibitors and Risk for Recurrent Clostridium difficile Infection

Abstract: Proton pump inhibitor use during incident CDI treatment was associated with a 42% increased risk of recurrence. Our findings warrant further studies to examine this association and careful consideration of the indications for prescribing PPIs during treatment of CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
149
1
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(166 citation statements)
references
References 60 publications
3
149
1
13
Order By: Relevance
“…Not surprisingly, the risk for rCDI was also greater among patients previously on fluoroquinolones (RR 1.42; 95 % CI 1.28-1.57; P \ .00001) [57]. While Linsky et al found a 42 % increased risk of rCDI with PPI use during incident CDI treatment, a study by Freedberg et al found no such association, instead noting a trend for reduced rCDI with PPI therapy, consistent with reports by Rotramel and colleagues [54,58,59]. Nevertheless, PPIs have been shown to affect the gastric microbiota [60], and a small pilot study recently found that PPI use decreased the diversity of the colonic microbiota [61]; as such, the effects of PPIs on the gut microbiome and rCDI warrant further investigation.…”
Section: Recurrent C Difficile Infection (Rcdi)supporting
confidence: 65%
“…Not surprisingly, the risk for rCDI was also greater among patients previously on fluoroquinolones (RR 1.42; 95 % CI 1.28-1.57; P \ .00001) [57]. While Linsky et al found a 42 % increased risk of rCDI with PPI use during incident CDI treatment, a study by Freedberg et al found no such association, instead noting a trend for reduced rCDI with PPI therapy, consistent with reports by Rotramel and colleagues [54,58,59]. Nevertheless, PPIs have been shown to affect the gastric microbiota [60], and a small pilot study recently found that PPI use decreased the diversity of the colonic microbiota [61]; as such, the effects of PPIs on the gut microbiome and rCDI warrant further investigation.…”
Section: Recurrent C Difficile Infection (Rcdi)supporting
confidence: 65%
“…11,12 Furthermore, other studies have found that, after controlling for important confounders such as age, comorbid conditions, prior history of CDI, antibiotic exposure, and hospitalization, use of PPI or H 2 blockers was not associated with the risk of developing CDI. 13,14 With respect to outcomes, 3 retrospective studies have found an increased risk of recurrent CDI in patients taking a PPI, [15][16][17] although a subgroup analysis of a large randomized controlled trial did not find a difference in the rates of recurrent CDI in patients with or without exposure to PPI and H 2 receptor antagonists. 18 We performed a populationbased study to examine outcomes in patients with CDI who were or were not receiving acid suppression medications at the time of CDI.…”
mentioning
confidence: 99%
“…Although generally well tolerated, PPI can cause serious adverse reactions. Their short-term use has been associated with infections such as community-acquired pneumonia [18][19][20][21] or Clostridium difficile diarrhea [22,24] due to low gastric acidity, and with a loss of efficacy of clopidogrel as a result of drug interaction [25][26][27][28][29][30]. Longterm use has been related to increases in hip fractures [31][32][33], delayed diagnosis of gastric cancer and increased risk of all-cause mortality [34,35].…”
mentioning
confidence: 99%